Perancangan Sistem Kendali Rumah Pintar Berbasis Arduino - Sitompul, Artaulima; Hotma Pangaribuan (LPPM Universitas Putera Batam, 2024)
The house can act as a place to shelter, rest, gather with family. However, there are times when homeowners often feel worried because they cannot monitor their house thoroughly, especially if it has been abandoned for a long time. Therefore, we need a control device that operates automatically or manually to monitor the condition of the house and can control it remotely. Arduino-Based Smart Home Control